Tax audit: the procedure and the identification of errors in the calculation of the budget (Journal of Economic Research & Business Administration, 2016)
In accordance with the requirements of Code РК «About taxes and other obligatory payments in a budget», put in an operation from January, 01, 2013, every enterprise or organization must work out and confirm tax registration politics. Key elements in a current tax audit are a correct calculation of the fiscal accounting and timely inpayment of sums of taxes. The aim of the fiscal accounting must be not minimization of separate taxes, and increase of acuestss of enterprise after tax payment. Taxes influence on each other in connection with that their tax bases can intersect. This position leaders that accept decision in area of financially-economic activity of organization taking into account possible tax consequences must constantly mean. On the preliminary stage of tax audit determined: basic principles, stages and going near realization of tax audit; bases of mutual relations of public accountant organization with tax organs during implementation of tax audit; it is responsibility of parties during realization of tax audit; order of realization and registration of results of the special public accountant job processing on tax questions. In an order to assume complete responsibility, a public accountant must find out all errors of client on taxes. And it means that it is necessary to check absolutely everything.
Keywords: tax audit; obligations; tax payment; calculation of taxes.